1990
DOI: 10.1007/bf01742493
|View full text |Cite
|
Sign up to set email alerts
|

Mouse tumors are heterogeneous in their susceptibility to syngeneic lymphokine-activated killer cells and delineate functional subsets in such effectors

Abstract: We have analyzed whether lymphokine-activated killer (LAK) cells, generated from C57BL/6J (B6) spleen cells at different times after recombinant interleukin-2 (rIL-2) culture, could be heterogeneous in their ability to lyse a variety of tumor targets. When tested 3 days after exposure to 250 U/ml rIL-2 (day-3 LAK cells) a significant lysis was detected with the natural-killer(NK)-sensitive YAC lymphoma, the NK-resistant P815 mastocytoma, three different syngeneic melanomas and a syngeneic fibrosarcoma (group 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…It has been previously shown that M5076 tumour cells are sensitive to LAK cell lysis in vitro [21] and in our study a slight increase of LAK cell activity has been found in the spleen of M5076-bearing mice following rlL-2 treatment (data not shown). Therefore, one should consider that the number of LAK cells generated in vivo after rlL-2 treatment is insufficient or that these effectors are not able to infiltrate metastases at the liver site and/or to express a cytotoxic activity.…”
Section: Discussioncontrasting
confidence: 46%
“…It has been previously shown that M5076 tumour cells are sensitive to LAK cell lysis in vitro [21] and in our study a slight increase of LAK cell activity has been found in the spleen of M5076-bearing mice following rlL-2 treatment (data not shown). Therefore, one should consider that the number of LAK cells generated in vivo after rlL-2 treatment is insufficient or that these effectors are not able to infiltrate metastases at the liver site and/or to express a cytotoxic activity.…”
Section: Discussioncontrasting
confidence: 46%
“…It is possible that LAK cells derived from NK cells use different target recognition structures from LAK cells derived from T cells. The hypothesis is supported by Sensi et al [15], who have shown that separate LAK effectors with different target cell recognition structures appear in IL-2-stimulated cultures with different time kinetics. It was observed by the same authors that the tumour cells are heterogeneous in their susceptibility to different LAK subpopulations.…”
Section: Discussionmentioning
confidence: 83%
“…Effectors are also generally classified as bearing either NK or T-cell surface markers, the latter having a greater lytic ability towards modified self cells, whereas NK-like LAK cells have superior lytic activity against culmred mmour lines [2,3,9]. Further, the kinetics of LAK growth have been examined and the expansion of LAK effectors with T-celllike phenotypes has been shown to increase with increasing culture periods, there being relatively few T-cell-like LAK cells at 3 days and a significant increase in their number by 7 days [1, 3,9,19]. It should be noted that these studies were performed using a standard medium supplemented with fetal calf serum; however, the LAK cells grown in AIM-V in the experiments reported here killed modified self targets poorly regardless of culture period.…”
Section: Methodsmentioning
confidence: 99%